(untitled) - Rosecrance, Richard N. (New York, 1985)
Book combines international relations theory with economics and the business model of the virtual corporation to describe how virtual states arise and operate, and how traditional powers will relate to them
Keywords: Commerce,Thương mại; History,Lịch sử; 20th century,Thế kỷ 20